SEXUAL EDUCATION AND PROMOTING GENDER EQUITY IN FACE OF DOMESTIC VIOLENCE AGAINST WOMEN - Marsico Azadinho, Mariana Passafaro [UNESP]; Oliveira, Angelita de Lima [UNESP]; Costa Milani, Debora Raquel da [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
Violence against women is one of the main forms of violation of human rights. According to the World Health Organization, Brazil ranks 5th in the countries that kill the most women in the world in the domestic and family context. This violence stems from a prejudiced, discriminatory, patriarchal, sexist and racist culture. To combat it, it is necessary, in addition to effective public policies, the integration of the Public Power with the areas of education, through educational actions that disseminate human rights and the ethical values of unrestricted respect for the dignity of the human person with the perspective of gender. In this sense, by means of a bibliographic survey, with a critical analysis of the theme addressed, this work aims to highlight the importance of sex education and the promotion of gender equity in the educational process of learning and socialization, concluding that this education contributes with the formation of critical thinking and with social development and collaborates with the construction of an egalitarian culture, with gender equality and facing all forms of violence, discrimination and prejudice against women.
Keywords: Sex education; Gender equity; Violence against women